Development and validation of food poisoning outbreak costing tool (MyFPO-CT) and cost analysis of food poisoning outbreak investigation management - Md Akhir, Mohd Yusuf (2022)
Background Food poisoning outbreak investigation management carried out by public health authorities require extensive resources. Information on cost analysis may assist public health authorities determine optimal intervention and plan management. There is a need for cost assessment of food poisoning outbreak investigation management. A costing tool that reflects an actual process of field investigation and outbreak management by public health authorities is needed for costing and budgeting purposes. Objectives This study aims to develop and validate a food poisoning outbreak costing tool (MyFPO-CT) and carry out program cost analysis of food poisoning outbreak investigation management. Methodology The study consists of two phases which Phase 1 developed and validated a new costing tool, meanwhile, Phase 2 involved cost analysis of food poisoning outbreak investigation management. The development of the MyFPO-CT was guided by the Costing of Health Services for Provider Payment framework from the Joint Learning Network for Universal Health Coverage. Microsoft Excel was the chosen platform due